Investigation of herpes simplex virus type 2 seroprevalence in all age groups (Annals of Medical Research, 2022)
Objective: Herpes simplex virus type 2 (HSV-2) is one of the most common causes of sexually transmitted genital infections and remains latent in neuronal cells for the lifetime of humans. In this retrospective study, it was aimed to determine the seroprevalence of HSV-2 and to evaluate its relationship with age and gender.Materials and Methods: In this study, 976 serum samples sent to Virology Laboratory between October 2016 and December 2018 were evaluated. HSV-2 IgM and IgG antibodies were tested with VirClia EIA/CLIA device by using a commercial kit.Results: Median age of 976 patients included in the study was 31 (0-88). Forty-three point three percent (423) of the patients were male. HSV-2 IgM was found in 0.3% (3/976) of the patients and HSV-2 IgG was found in 3.7% (36/976). HSV-2 IgG was detected in 2.8%  of male patients (12/423)  and 4.3% (24/553) of female patients (P = 0.120). The highest HSV-2 IgG seropositivity rate was between the ages of 40 and 59 in both genders (8.3% in males and 8.3% in females) (P = 0.010 and P = 0.250 respectively).Conclusion: The HSV-2 IgG seropositivity rates we detected in this study were consistent with other study data in our country and in the world. Studies on HSV-2 IgG seroprevalence and determination of the age groups at risk will be guides for public health studies aimed for protection against HSV-2 infection.
Keywords: herpes simplex virus; seroprevalence; HSV type 2 IgG